Posttraumatic Stress and Myocardial Infarction Risk Perceptions in Hospitalized Acute Coronary Syndrome Patients - Edmondson, Donald; Shaffer, Jonathan A.; Denton, Ellen-ge; Shimbo, Daichi; Clemow, Lynn (Frontiers in Psychology, 2012)
Posttraumatic stress disorder (PTSD) is related to acute coronary syndrome (ACS; i.e., myocardial infarction or unstable angina) recurrence and poor post-ACS adherence to medical advice. Since risk perceptions are a primary motivator of adherence behaviors, we assessed the relationship of probable PTSD to ACS risk perceptions in hospitalized ACS patients (n= 420). Participants completed a brief PTSD screen 3-7 days post-ACS, and rated their 1-year ACS recurrence risk relative to other men or women their age. Most participants exhibited optimistic bias (mean recurrence risk estimate between “average” and “below average”). Further, participants who screened positive for current PTSD (n=15) showed significantly greater optimistic bias than those who screened negative (p< .05), after adjustment for demographics, ACS severity, medical comorbidities, depression, and self-confidence in their ability to control their heart disease. Clinicians should be aware that psychosocial factors, and PTSD in particular, may be associated with poor adherence to medical advice due to exaggerated optimistic bias in recurrence risk perceptions.